Odpowiedzi

2010-03-24T15:58:23+01:00
A)2x-5=87
2x=87+5
2x=92 / :2
x=46

b)4(2x-3)=6-x
8x-12=6-x
8x+x=6+12
9x=18 / :9
x=2

c)3x-6=87
3x=87+6
3x=93 /:3
x=31

d)5(2x-3)=3+x
10x-15=3+x
10x-x=3+15
9x=18 /:9
x=2

;))
1 5 1
2010-03-24T15:59:32+01:00
A. 2x-5=87
2x=87+5
2x=92 /:2
x= 46
b. 4(2x-3)= 6-x
8x-12=6-x
9x=18 /:9
x=2
c. 3x-6=87
3x=87+6
3x=93 /:3
x= 31
d. 5(2x-3)=3+x
10x-15=3+x
9x=18 /:9
x=2
2010-03-24T16:03:46+01:00
A)2x-5=87
2x=87-5
2x= 82/5
x=16,4

b)4(2x-3)=6-x
2x-x=4-3-6
2x=-5/2
x=-2,5

c)3x-6=87
3x=87-6
3x=81/3
x=3

d)5(2x-3)=3+x
5*2x-3=3x+3
2x+3x=5*3+3
5x=24/5
x=4,8
nie wiem czy dobrze jak zle to sorki.; (